2023
DOI: 10.12997/jla.2023.12.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Harms of COVID-19 Vaccines in Cardiovascular Disease: A Comprehensive Review

Abstract: Patients with a history of cardiovascular disease (CVD) who contract coronavirus disease 2019 (COVID-19) tend to have a worse prognosis and more severe cardiovascular side effects. COVID-19 vaccines, which are intended to prevent COVID-19, may also potentially reduce the severity and complications (including cardiovascular sequelae) of COVID-19, especially in patients with a history of CVD. However, there have also been reports of cardiovascular side effects from COVID-19 vaccines of various brands and types. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Cardiovascular events such as myocardial infarctions, strokes, embolism, and others have been studied, and while some studies have suggested increased reporting rates of these events [ 41 , 42 ], others have not found such an association [ 36 , 43 , 44 , 45 , 46 , 47 ]. While some authors have previously suggested that mRNA vaccines have been associated with increased reports of adverse cardiovascular reactions than other types of SARS-CoV-2 vaccines, it is true that the strongest association remains thus far with myocarditis and pericarditis, and the evidence regarding the association of SARs-CoV-2 vaccines with cardiovascular outcomes still remains to be elucidated [ 48 ]. In our previous VigilVacCOVID study, we detected some cases of syncope, hypertension, hypotension, chest pain, cold sweat, and tachycardia as unsolicited ARs; similar findings were previously reported as potential cardiovascular adverse effects in other studies [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular events such as myocardial infarctions, strokes, embolism, and others have been studied, and while some studies have suggested increased reporting rates of these events [ 41 , 42 ], others have not found such an association [ 36 , 43 , 44 , 45 , 46 , 47 ]. While some authors have previously suggested that mRNA vaccines have been associated with increased reports of adverse cardiovascular reactions than other types of SARS-CoV-2 vaccines, it is true that the strongest association remains thus far with myocarditis and pericarditis, and the evidence regarding the association of SARs-CoV-2 vaccines with cardiovascular outcomes still remains to be elucidated [ 48 ]. In our previous VigilVacCOVID study, we detected some cases of syncope, hypertension, hypotension, chest pain, cold sweat, and tachycardia as unsolicited ARs; similar findings were previously reported as potential cardiovascular adverse effects in other studies [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…While these vaccines have proven their efficacy in clinical trials, many case reports and studies have reported increased risk of different cardiovascular and haematological (CVDH) adverse events such as thrombocytopenia, venous thromboembolism, myocardial infarction and stroke for multiple types of vaccines used globally 11 13 . There is limited evidence on the safety profile of these vaccines in real-world setting at a regional population level for risk of major CVDH events 14 . In addition, the ethnic diversity in the resident population and high vaccination rates in Abu Dhabi provide a unique opportunity to evaluate the safety profile of these vaccines in a diverse population in addition to providing important regional data 15 .…”
Section: Introductionmentioning
confidence: 99%